Descarga de vinazas de la destilería San Ramón, comunidad de Agua Fría y, la calidad de su entorno - Dueñas Cevallos, Freddy Andres (2019)
The developed study responded to the problem formulation regarding the relationship between the discharge of vinasse from the San Ramón distillery, located in the community of Agua Fría, municipality of Junín and the quality of its surroundings; rejecting the research hypothesis and establishing that the discharge is positively related to the quality of the territory environment. To establish this rejection, it was proceeded to the weighting of the vinasse discharge, through the flow and concentration measurements of pollution indicating parameters such as Hydrogen Potential (pH), Electrical Conductivity (CE), Total Solids (ST), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Phosphate (PO43-), Nitrate (NO3-), Nitrite (NO2-) and Ammonium (NH4+); all as part of the independent variable. As a dependent variable, the quality of the distillery's environment was determined, through the observation guide instrument applied in situ and interview guide to a sample of 91 people, representative of the population over 18 years of age; thus, parameters such as air odor, loss of vegetation cover, the presence of vectors and water quality in the Agua Fría estuary, as well as the causes of their negativities that hovered around 94%, in terms of observation technique in situ were characterized and 75% according to the interview technique. Considering the results, it was evident, with very high confidence under any statistical analysis, that both the concentrations and the pollutant loads discharged into the environment by the San Ramón distillery are well above the maximum allowed by the regulations, both nationally and internationally. This ocurred with all mentioned parameters. With respect to the Hydrogen Potential, pH, the values obtained were in the frankly acid range, well below what is allowed by the regulations. It is recommended the treatment of vinasse by an anaerobic system, taking advantage of biogás generation.